Protective effects of Bifidobacterium longum subsp. longum BL21 against cyclophosphamide-induced reproductive dysfunction in zebrafish - Yao Dong; Jiazhi Zhou; Hairui Tian; Zhonghui Gai; Kang Zou; Quanwei Wei; Mei Han (Scientific Reports)
Abstract This study aimed to investigate the effects of probiotic Bifidobacterium longum subsp. longum BL21 on reproductive health in zebrafish (Danio rerio), focusing on hormonal modulation, sperm vitality, and overall reproductive function improvement. Adult male zebrafish of the wild-type AB strain were divided into four groups: control (CTL), model control with cyclophosphamide-induced oligospermia (CS), probiotic-treated (BL21), and a positive control treated with clomiphene citrate (CC). All groups, except CTL, were exposed to cyclophosphamide from day 1 to day 9 to induce reproductive dysfunction, with subsequent monitoring until day 16. Key metrics assessed included body and testicular weight, sperm vitality, male courtship behavior, hormone levels, sperm DNA fragmentation, and gene expression of PCNA, NANOG, ZBTB16, mTOR, DDX4, CYP26A1, and ALDH1A2. In this study, BL21 demonstrated significant therapeutic potential in treating reproductive dysfunction in zebrafish. Metabolomic analysis revealed that BL21 influenced crucial pathways, notably upregulating mTOR signaling and isoflavone biosynthesis, while downregulating the TCA cycle and pyruvate metabolism, suggesting a broad biochemical impact. The probiotic treatment notably improved testicular weight (p < 0.01) and sperm count and vitality (p < 0.001) compared to the cyclophosphamide-induced model control, underscoring its efficacy in enhancing reproductive parameters. Additionally, BL21 intervention led to a marked increase in chasing behavior and sex hormone levels, surpassing those of the positive control. The treatment also significantly reduced sperm DNA fragmentation (p < 0.001) and increased the expression of genes crucial for spermatogenesis and testicular function (p < 0.05), confirming its potential to restore reproductive health at multiple biological levels. These results highlight the promise of BL21 as a multi-faceted agent for improving reproductive health, warranting further investigation in clinical settings. Probiotic BL21 enhances reproductive parameters in zebrafish by modulating hormone levels, improving sperm quality, and positively affecting reproductive behavior. These findings suggest potential therapeutic applications of probiotics in managing reproductive health issues.